Analysis of the tension chord in the flexural response of concrete elements: Methodology and application to weft-knitted textile reinforcement. (15th June 2022) - Lee, Minu; Mata-Falcón, Jaime; Kaufmann, Walter
Highlights: A methodology to assess the stress–strain relationship of the tension chord in reinforced concrete beams is proposed. The flexural response of knitted textile reinforced concrete was experimentally investigated to validate the methodology. The comparison with corresponding uniaxial tension tests showed good agreement of the load-deformation and crack behaviour. Weft-knitted textile reinforcement, even when attached to the bottom edge, exhibited a beneficial post-cracking behaviour. The Tension Chord Model allows predicting the load-deformation behaviour, tension stiffening effect and crack kinematics. Abstract: The use of high-strength fibrous materials offers great potential to serve as the main reinforcement in the flexural response of lightweight concrete structures. Specifically, weft-knitted textile reinforcement allows creating complex geometries (i.e. doubly curved or folded) and introducing straight inlays as well as spatial features such as ribs within the fabric to enhance the bond conditions between the reinforcement and the concrete. While the evaluation of uniaxial tension tests to characterise the mechanical behaviour is usually straightforward, the vast majority of bending tests of textile reinforced concrete elements in the literature are limited to load–displacement data, which does not give direct information on the mechanical behaviour and makes it difficult to compare specimens with different geometries or reinforcement contents. This study presents a methodology based on digital image correlation measurements to directly assess the response in the tension chord of reinforced concrete beams in four-point bending. This methodology was applied and validated in an experimental campaign consisting of 16 bending tests with weft-knitted textile reinforcement. Various fibre materials, coating types and specimen geometries were tested, and the results were compared to corresponding uniaxial tension tests with the same type of reinforcement, generally showing a good agreement in the load-deformation behaviour and the crack kinematics. However, the textile reinforcement could not be utilised to the tensile strength obtained in uniaxial tension since all bending beams failed prematurely either in a combined bending-shear type failure (for most of the cement paste-coated textiles) or due to the delamination of the textile within a shear crack (for all epoxy-coated textiles). The Tension Chord Model with an assumed constant bond-slip relationship and an equivalent reinforcement ratio in bending yielded a good prediction of the stress–strain relationship, the tension stiffening effect, the crack widths and spacing.